2012
DOI: 10.1039/c2ob00042c
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic synthesis, antibacterial activity and structure–activity properties of the pyroglutamate core of oxazolomycin

Abstract: Biomimetic intramolecular aldol reactions on oxazolidine templates derived from serine may be used to generate densely functionalised pyroglutamates, which are simpler mimics of the right hand side of oxazolomycin. Some of the compounds from this sequence exhibit in vivo activity against S. aureus and E. coli, suggesting that pyroglutamate scaffolds may be useful templates for the development of novel antibacterials, and cheminformatic analysis has been used to provide some structure-activity data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…The preservation of the chirality of serine and the stereochemical outcome at C2 indicated that MOC and DKR were active during the reaction. Notably, in previous reports by Moloney, similar aldol reactions of Seebach's oxazolidine substrates 14 (Scheme ) proceeded with low stereoselectivity, which highlights the efficiency of our MOC aldol ring closure of the oxaproline substrate 7 .…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…The preservation of the chirality of serine and the stereochemical outcome at C2 indicated that MOC and DKR were active during the reaction. Notably, in previous reports by Moloney, similar aldol reactions of Seebach's oxazolidine substrates 14 (Scheme ) proceeded with low stereoselectivity, which highlights the efficiency of our MOC aldol ring closure of the oxaproline substrate 7 .…”
Section: Methodssupporting
confidence: 70%
“…This type of aldol reaction has been proposed as a plausible step in the biosynthetic pathway towards oxazolomycins . In turn, it was envisioned that 7 could be traced back to the known β‐keto acid 8 and d ‐serine. If the principles of “memory of chirality” (MOC) and “dynamic kinetic resolution” (DKR) were applied to the aldol reaction of 7 , as in our previous total synthesis of (−)‐penibruguieramine starting from l ‐proline, the asymmetric synthesis of 3 could be achieved from d ‐serine without the aid of external chiral influences.…”
Section: Methodsmentioning
confidence: 99%
“…In order to demonstrate that such intermediates could be used to perform the desired ring closing aldol reaction, one of them (6a) was hydrolysed to acid 7 and converted to malonamide 8 by DCC coupling with oxazolidine 1. Furthermore, during the course of this work, we found that acyl Meldrum's acids 5b-d could be opened directly with oxazolidine 1 (R ¼ H), 15,16,19,20 giving malonamides 9a-c very efficiently; these sequences provided access to variously substituted analogues replacing the methoxy group at the chain terminus of 8. We also expected that intermediates of type 6 would prove to be pivotal, since alkylation at either or both of the a-and g-positions using standard conditions should be possible, providing access to diversely functionalised pyroglutamates aer cyclisation.…”
mentioning
confidence: 98%
“…The combined organic layers were washed with brine (20 mL), dried and concentrated in vacuo to give 5c as a red solid(1.49 g, 93%); mp 112-115 C; n max (lm) 3000, 1741, 1648; d H (400 MHz, CDCl 3 ) 1.73 (6H, s, CH 3 ), 4.37 (2H, s, CH 2 ), 7.27 (2H, d, J 8.3, C(2 0 )H, C(6 0 )H), 7.46 (2H, d, J 8.3, C(3 0 )H, C(5 0 ) H); d C (100 MHz, CDCl 3 ) 26.8 (CH 3 ), 40.2 (CH 2 ), 91.5 (C(5)), 105.1 (C(2)), 121.7 (C(4 0 )), 131.3 (C(2 0 ), C(6 0 )), 131.8 (C(3 0 ), C(5 0 )), 133.0 (C(1 0 )), 170.5 (C(4), C(6)), 193.8 (C]O); m/z (ESI À ) 388 ([M À H] À , 100%); HRMS (ESI + ) C 14 H 13 BrO 5 + ([M + Na] + ) requires 362.9839, 364.9829, found 362.9826, 364.9807. 5-(1 0 -Hydroxy-2 0 -(phenylthio)ethylidene)-2,2-dimethyl-1,3-dioxane-4,6-dione 5d Following general procedure A, pyridine (0.86 mL, 10.7 mmol) and Meldrum's acid (771 mg, 5.35 mmol) in DCM (25 mL) were combined with a solution of acid chloride 4d (1.00 g, 5.35 mmol) in DCM (5 mL) to give 5d as an orange oil (1.62 g, quant); n max (lm) 3000, 1737, 1666; d H (400 MHz, CDCl 3 ) 1.67 (6H, s, CH 3 ), 4.38 (2H, s, C(2 0 )H 2 ), 7.28-7.32 (3H, m, Ph), 7.47-7.51 (2H, m, Ph), 14.57 (1H, br s, OH); d C (100 MHz, CDCl 3 ) 26.8 (CH 3 ), 36.4 (C(2 0 )), 91.1 (C(5)), 105.2 (C(2)), 127.0, 128.0, 132.1 (o,m,pPh), 133.5 (i-Ph), 170.4 (C(4), C(6)), 192.1 (C(1 0 )); m/z (ESI À ) 293 ([M À H] À , 40%); HRMS (ESI À ) C 14 H 13 O 5 S À ([M À H] À ) requires 293.0489, found 293.0489.tert-Butyl 4-methoxy-3-oxo-butanoate 6a (ref 15). Following general procedure B, a solution of 5a (3.5 g, 16.2 mmol) in 1 : 1 toluene-t BuOH (36 mL) was stirred at reux for 2 h. The mixture was cooled to rt and concentrated in vacuo to give 6a as a dark brown liquid (2.2 g, 73%);…”
mentioning
confidence: 99%
“…Natural products have unique structures, which often are environmentally compatible and tend to have a greater biological activity. L‐Pyroglutamic acid (L‐pGlu) is a natural amino acid, and in the past decade, pyroglutamic acid analogues have shown great biological importance, having Gram‐negative antibacterial activity , anti‐inflammatory activity , and human farnesyltransferase inhibitory activity . In our continuous efforts to develop new antifungal compounds and also motivated by these findings, we continued to explore new L‐pyroglutamic acid (a) and γ‐lactam (b) derivatives, towards finding lead compounds.…”
Section: Conditions Of Optimal Separation Of the Six Analytesmentioning
confidence: 99%